2001
DOI: 10.1021/jf001369a
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Seasonal Variation of the Essential Oil from Leaves and Peel of a Cretan Lemon Variety

Abstract: The essential oil of leaves and peel from the Cretan variety Zambetakis (Citrus limon) was obtained by steam distillation with a Clevenger apparatus. The essential oil was subjected to GC-MS analysis, and 35 substances were identified. The main component in both essential oils was limonene. beta-Pinene, myrcene, neral, geranial, neryl acetate, geranyl acetate, and beta-caryophyllene have been identified in the leaf oil. The peel oil contained gamma-terpinene, beta-pinene, myrcene, neral, and geranial. The quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(92 citation statements)
references
References 11 publications
6
82
2
2
Order By: Relevance
“…Most of the compounds identified in Citrus peel oils were found to be hydrocarbons in nature (Ayoola et al, 2008). The major constituents of Citrus peel oils investigated by Vekiari et al, (2002) (Pavithra et al, 2009). D-limonene, linalool or citral are major attributors for the antimicrobial capacity of Citrus peel oils.…”
Section: Chemical Composition By Gc-ms Analysismentioning
confidence: 99%
“…Most of the compounds identified in Citrus peel oils were found to be hydrocarbons in nature (Ayoola et al, 2008). The major constituents of Citrus peel oils investigated by Vekiari et al, (2002) (Pavithra et al, 2009). D-limonene, linalool or citral are major attributors for the antimicrobial capacity of Citrus peel oils.…”
Section: Chemical Composition By Gc-ms Analysismentioning
confidence: 99%
“…Citrus limon é rico em limoneno, β-pineno, γ-terpineno, terpinoleno, neral e geranial (Vekiari et al, 2002;Bisset;Wichtl, 2001;Ghelardini et al, 1999). Dados farmacológicos: O óleo volátil causou inibição no crescimento de Candida albicans (Ezzat, 2001).…”
Section: Citrus Limon (L) Osbeck (Rutaceae) -Constituintes Químicos:unclassified
“…The seeds are used for medicinal purposes (Shah et al, 2010) and the seed kernel oil has been found to contain phenolic compounds, hence is widely used in cosmetics industries (Soong and Barlow, 2006). Key lime (Citrus aurantiifolia) seeds have been employed in folk medicine for the treatment of diseases and the seed oil is used in cosmetics industries for the production of perfumes (Vekiari et al, 2002). African star apple (Chrysophyllum albidum) seeds have a shiny hard brown casing which feels like plastic that allows them to be viable for years and used for local games (Akpabio et al, 2012).…”
Section: Introductionmentioning
confidence: 99%